FORMATION OF INTERCULTURAL VALUES ​​ORIENTATIONS OF SENIOR PUPILS BY MEANS OF STUDYING A FOREIGN LANGUAGE - Halian, Ihor (PSYCHOLOGICAL JOURNAL, 2018)
The article presents the results of the study of development of intercultural values orientation of senior pupils by means of studying at foreign language. The formation of intercultural values was evaluated according to such criteria as: the availability of knowledge about the culture of the country of language practice, sufficient for establishing relations with its representatives; tolerance to the representatives of the culture of the country of language practice, orientation towards cooperation with them; ability to select adequate situations of communication behaviour model. To study the state of development of intercultural values of senior pupils we used a set of psychodiagnostic techniques that are relevant to the isolated criteria. 51 senior pupils (n = 51) of secondary schools were involved to the experiment, which lasted for two academic years. Establishment of the initial level of development of intercultural values orientations in senior pupils influenced creation of methodical and psychological measures for their development. The basis of the developmental program were English classes, tasks creation, training, work on the Internet, etc. During the implementation of the study program there was a combination of the gradual formation of intercultural value orientations of senior pupils and the structure of the intercultural educational situation, which is the environment for the implementation of this process. The nature of tasks and exercises was determined according to the following stages of formation of the intercultural values of pupils: the acquisition of cultural values of the country of language practice; personal transformations based on personal values; planning further personal development. On the basis of certain criteria of the formation of intercultural values orientations and their level of manifestation, the types of levels of formation of intercultural values orientations are determined, namely: knowledge (low); situational-effective (average) and practical (high). It is stated that the process of mastering the language should be considered as an integral component of the formation of values of culture of the personality of pupils.